Densities and Distribution of Vitellariaparadoxa C.F.Gaertn. and Parkia biglobosa (Jacq.) R.Br.ex G.Don. in Agro-ecosystems in Oyo State, Nigeria (2012)
Population increase has led to increased pressures on many socioeconomically and ecologically important tree species including Vitellaria paradoxa C.F.Gaertn.and Parkia biglobosa (Jacq.) R.Br.ex G.Don. This portends great threats to the continued existence of such species including the myriads of goods and services they provide. There is need to put on record, scientific evidence of the current status of these species in order to draw attention to the pressures on their populations and the need for deliberate actions for their conservation and sustainable management. We assessed densities and distribution of Vitellaria paradoxa and Parkia biglobosa in some agro ecosystems in Oyo State, Nigeria with a view to generating information on the current stocking of the species in the various ecosystems and provide base line data for subsequent resource monitoring and sustainable management planning. Oyo State was stratified into three agro-ecological zones viz: dry-woodland/Southem Guinea savanna, moist-woodland/derived savanna and rainforest. A multistage sampling procedure was used in collecting data on densities and distribution of Vitellaria paradoxa and Parkia biglobosa in the agro ecosystems through field survey. Descriptive statistics, cross tabulation, simple t-test and analysis of variance (ANOVA) were used to analyze the data. Student’s t-test and analysis of variance indicate that there was no significant difference at 5% level of probability in the densities of V paradoxa and P. biglobosa in the cultivated and fallow land. Potential mother trees for regeneration were found mainly on crop farms while younger trees dominate the fallow plots. This is an indication of extraction of older trees on fallow plots apparently for domestic energy supplies. It is recommended that the management of V. paradoxa and P. biglobosa should be intensified through enrichment planting and deliberate cultivation in plantations in order to meet the high demand pressures on their populations